Intravenous infusion of salbutamol in severe acute asthma. Issue 6119 (22nd April 1978) - Johnson, A J; Spiro, S G; Pidgeon, J; Bateman, S; Clarke, S W
Abstract : Out of 62 asthmatic patients admitted to hospital with an acute exacerbation of their disease, those whose symptoms had not sufficiently improved 15 minutes after an initial intensive regimen were randomly allocated to receive an intravenous infusion of either salbutamol 10 microgram/min (20 patients) or aminophylline 1 mg/min (19 patients). During the infusions, which lasted 36 hours, peak expiratory flow rates and spirometric values improved in both groups, but differences between the groups did not achieve statistical significance. Although salbutamol may be infused safely for a prolonged period to patients with acute asthma, it has no particular advantage over aminophylline. Furthermore, in patients who respond poorly to initial intensive treatment the subsequent infusion of a bronchodilator may not increase the rate of recovery from the rate that would occur naturally.